2019
DOI: 10.1093/infdis/jiz130
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Microscopic and Submicroscopic Parasitemia During Pregnancy on Placental Malaria in a High-Transmission Setting in Uganda

Abstract: In pregnant women assessed for parasitemia every 28 days, the risk of placental malaria increased in a dose-response relationship with both increasing frequency and density of parasitemia; however, even women with only submicroscopic parasitemia were at risk for placental malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 33 publications
5
23
0
Order By: Relevance
“…past and chronic infection) is associated with a higher risk of LBW or IUGR [16,19,20]. The risk of placental malaria is, in turn, affected by gravidity, age, number of malaria infections, and parasite density [16,47], which was confirmed in this IPD meta-analysis (with the exception of frequency of parasitaemia, which could not be assessed). Additionally, a higher risk of placental malaria was observed in women with higher body temperature before treatment, which can be a surrogate for the severity of the infection; inflammatory cytokines causing fever (e.g.…”
Section: Discussionsupporting
confidence: 66%
“…past and chronic infection) is associated with a higher risk of LBW or IUGR [16,19,20]. The risk of placental malaria is, in turn, affected by gravidity, age, number of malaria infections, and parasite density [16,47], which was confirmed in this IPD meta-analysis (with the exception of frequency of parasitaemia, which could not be assessed). Additionally, a higher risk of placental malaria was observed in women with higher body temperature before treatment, which can be a surrogate for the severity of the infection; inflammatory cytokines causing fever (e.g.…”
Section: Discussionsupporting
confidence: 66%
“…Heterogeneity in the study designs, population demographics, surveillance protocols, diagnostic and treatment methodologies, and regional malaria characteristics may explain at least some of the discrepancies in these studies. Recently, an analysis of a separate cohort of women in Uganda found that burden of infection and timing of parasitemia impact risk for placental malaria, which is consistent with our ndings [32]. Our study suggests that the importance of timing of infection on the development of placental malaria may vary based on gravidity.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, an analysis of a separate cohort of women in Uganda found that burden of infection and timing of parasitemia impact risk for placental malaria, which is consistent with our findings. 32 Our study suggests that the importance of timing of infection on the development of placental malaria may vary based on gravidity. This finding may further explain why prior literature has painted an unclear picture of the impact of timing of infection on placental malaria.…”
Section: Discussionmentioning
confidence: 76%